Abundance Estimates in Carbon Star Envelopes. Issue Volume 14:Issue S343(2019) (August 2018) - Massalkhi, S.; Agúndez, M.; Cernicharo, J.
Abstract: The synthesis of dust grains mostly takes place in the circumstellar envelopes (CSEs) of asymptotic giant branch (AGB) stars. What are the precursor seeds of condensation nuclei and how do these particles evolve toward the micrometer sized grains that populate the interstellar medium? These are key questions of the NANOCOSMOS project. In this study, we carried out an observational study to constrain what the main gas-phase precursors of dust in C-rich AGB stars are.